The Importance of Islamic Religious Education in Building the Superior Character of the Younger Generation - Ilyas, Jaohari; Ahmad Fathurahman, Asep; Salsabila, Iis (Yayasan Mentari Madani, 2024)
This study aims to investigate the important role of Islamic religious education in shaping superior character in the younger generation. The focus is to understand how Islamic religious education can contribute in developing the morality, ethics, and values necessary to form qualified and noble moral individuals. This research uses qualitative and quantitative approaches by conducting a comprehensive literature review and case studies involving participants from various walks of life. Data were collected through interviews, observations, and analysis of documents related to Islamic religious education and character building of the younger generation. The results showed that Islamic religious education plays an important role in shaping superior character in the younger generation. Through a deep understanding of religious values, young people can internalize the principles of honesty, justice, compassion, and social responsibility. In addition, Islamic religious education also provides a strong foundation for developing attitudes of tolerance, respecting diversity, and strengthening religious identity. This study confirms that Islamic religious education has a strategic role in shaping superior character in the younger generation. The recommendations resulting from this study include expanding the Islamic religious education curriculum, increasing training for educators, and increasing the role of family and community in supporting the formation of character with integrity and ethics in the younger generation